MONITORING PELAKSANAAN PROYEK REVITALISASI RUANG PAVILIUN RUMAH SAKIT UMUM Dr. SOEROTO NGAWI DENGAN METODE NILAI HASIL - Nugroho, Meriana Wahyu (Reaktom : Rekayasa Keteknikan dan Optimasi, 2016)
Every construction project certainly has constraint and barrier, to limit every constraint occurs in project conduction then it needs supervision or monitoring in carrying out of building activity. This research uses value result method to determine the time needed to finish and cost needed up to the finishing project. Here, there are there are three indicators attentioned in using result value method, they are BCWS, BCWP, and ACWP. The monitoring result from result value method calculation is that the estimation of the last finishing job are 123 days three days late from the normal is that 120 days in finishing. Whereas the cost spends up to the finishing job is estimated Rp. 612.512.649,00 lower than the cost determined, and it can be guess that the company get profits.Key words: project monitoring, result value methode, time, and cost.